Digital Transformation and its Impact on Entrepreneurship in The Creative Industries - Wening Estiningsih; Mohamad Halilintar (Asian Journal of Social and Humanities, 2026)
This research aims to analyze the impact of digital transformation on entrepreneurship in Indonesia's creative industries. A qualitative approach was employed, drawing on a systematic literature review and statistical data analysis from credible sources, including government publications (Ministry of Tourism and Creative Economy, Coordinating Ministry for Economic Affairs, Central Statistics Agency) and academic journals. The results show that digital technology has opened new opportunities for creative entrepreneurs by providing broader distribution platforms, reducing operational costs, and enabling business model innovation. Indonesia's creative economy sector recorded a GDP value of Rp 1.28 quadrillion in 2022, absorbing 23.98 million workers. Digital platforms, such as marketplaces, have facilitated broader market access for small and medium enterprises. However, this transformation also presents various obstacles, such as gaps in digital infrastructure and limited technological literacy. This research concludes that digital transformation serves as the main catalyst for entrepreneurship growth in the creative industries, provided there is adequate infrastructure support and enhancement of digital capabilities among business actors.